Illegal motion - Stockley, Grif (New York : Ballantine Books, 1997)
In Arkansas, lawyer Gideon Page is hired to defend a black football player from a charge of rape. The accuser is a white cheerleader and the setting is a college where Page's daughter is a student, which complicates things as she is a feminist.
"A novel"--Cover.
Keywords: Trials (Rape) -- Fiction; Detective and mystery fiction